Islamic Extremism and the Challenges of Terrorism in the West African Sub-Region: Charting the Way Forward - Nte , Ngboawaji Daniel; Torru, Bianca Oyinkarebi; Isa, Awwal; Baba-Ahmadu, Abdulaziz (Indonesian Journal of Police Studies, 2021)
This study examines Islamic extremism, and the challenges of terrorism in the West African sub-region. This was achieved through a systematic review of the activities terrorist groups in West Africa and how they affect the African and indeed the global security space. Consequently, this burgeoning threat has necessitated a search for an effective solution to the sub-region’s security challenges as the region in recent times has become the flashpoint of incessant bombing, hostage-taking, killing of innocent civilians on a daily basis; leading to loss of businesses and property. The work employed an historical design and relied on primary and secondary sources of data- via the use of text books, journals, newspaper, official documents and internet sources. For the purpose of a theoretical framework, the study is guided by the frustration-aggression theory, which made it possible to discuss and apply relevant literatures that are centered on Islamic extremism, global security and the challenges of terrorism in West Africa. The study equally raised five research questions that were answered using qualitative data in the form of supportive literatures. The analysis of these literatures revealed among others; the challenges of terrorism in West Africa and the nexus between African terrorist organizations and other terrorist organizations around the globe. As part of the solution/ counter terrorism measures in West Africa, the study also reviewed the UN Global Counterterrorism Strategy (UNGC-T Strategy) and the UN General Assembly Resolution 1373 and 1612 on African Counter Terrorism Strategies. From the findings of this study, the following recommendations were made; the need for African States affected by acts of terrorism to reappraise their socio-economic conditions and political policies in other to improve on them, the creation of legal and institutional bodies to adjudicate on cases associated with terrorism, Government, through the religious advisory committee should map out sustainable strategies will encourage religious tolerance discourage any kind of preaching that involves criticism, condemnation and abuse of other religions and the adoption and implementation of the UNGC-T Strategies among others to ensure a peaceful and stable sub-region poised for economic growth and development.